2011
DOI: 10.3727/096368910x550215
|View full text |Cite
|
Sign up to set email alerts
|

The Secretory Profiles of Cultured Human Articular Chondrocytes and Mesenchymal Stem Cells: Implications for Autologous Cell Transplantation Strategies

Abstract: This study was undertaken to compare the phenotype of human articular chondrocytes (ACs) and bone marrow-derived mesenchymal stem cells (MSCs) after cell expansion by studying the spectrum of proteins secreted by cells into the culture medium. ACs and MSCs were expanded in monolayer cultures for some weeks, as done in standard cell transplantation procedures. Initially, the expression of cartilage signature genes was compared by real-time PCR. Metabolic labeling of proteins (SILAC) in combination with mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 39 publications
2
41
1
2
Order By: Relevance
“…Recent preclinical studies have reported that secretomes from MSC have the potential for treating some intractable diseases as acute myocardial infarction [16], fulminant hepatic failure [43], renal failure [44], [45], ischemic stroke [46], experimental autoimmune encephalomyelitis [47] and hypoxic brain injury [48] and for the repair of soft tissues [49]. Also, has been reported that MSC-CM has a very high potential for bone regeneration, mediated by the cooperative effects of cytokines such as IGF-1, TGF-ß1 [50], [51], VEGF, angiogenin [50], HGF (Hepatocyte growth factor) [51], BMP-1 [52], IL-6, IL-3, MCP-1 (Monocyte Chemoattractant Protein-1) and MCP-3 (Monocyte Chemoattractant Protein-3) [41]. These cytokines regulate several events of osteogenesis, angiogenesis, cell migration, proliferation, and osteoblast differentiation [50].…”
Section: Discussionmentioning
confidence: 99%
“…Recent preclinical studies have reported that secretomes from MSC have the potential for treating some intractable diseases as acute myocardial infarction [16], fulminant hepatic failure [43], renal failure [44], [45], ischemic stroke [46], experimental autoimmune encephalomyelitis [47] and hypoxic brain injury [48] and for the repair of soft tissues [49]. Also, has been reported that MSC-CM has a very high potential for bone regeneration, mediated by the cooperative effects of cytokines such as IGF-1, TGF-ß1 [50], [51], VEGF, angiogenin [50], HGF (Hepatocyte growth factor) [51], BMP-1 [52], IL-6, IL-3, MCP-1 (Monocyte Chemoattractant Protein-1) and MCP-3 (Monocyte Chemoattractant Protein-3) [41]. These cytokines regulate several events of osteogenesis, angiogenesis, cell migration, proliferation, and osteoblast differentiation [50].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the established trophic role of BMSC (Refs 72, 73), cultured ASC were shown to secrete a wide range of proteins (Ref. 74) into conditioned media that predominantly exert anti-apoptotic (Refs 75, 76, 77), immunomodulatory (Refs 78, 79, 80) and angiogenic (Refs 77, 81, 82) effects on co-cultured cell types.…”
Section: Comparison Of Trophic Activitymentioning
confidence: 88%
“…Only a few studies explored the secretome of undifferentiated MSCs [30]. It has been shown in a proteomic study that undifferentiated MSCs secrete a number of matrix components and matrix regulators in 2D cultures [31]; however, the expression of the regulation of these proteins by cellular interactions between MSCs and other cell types is not yet investigated. The current study is one of the first to explore the response and changes in the gene expression of MSCs in co-culture with other cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with the fact that FGF-1 concentration increased dramatically in the CM of co-culture pellets when compared with mono-cultures, we also concluded that not only expression but also secretion of FGF-1 is increased by the cross-talk between MSCs and hPCs. From literature, it can be deduced that both cells secrete a wide range of growth factors, cytokines, and extracellular matrix components into their surrounding environment [31]. Some of these molecules may form a feedback loop that stimulates the expression of FGF-1.…”
Section: Discussionmentioning
confidence: 99%